Bridging the gap: Enhancing sustainability in Harumanis mango farming through smart technologies and farmer readiness - Kunalan, Manishaa Devi; Chee Ann, Lim; Rahmat, Siti Rahyla (International Journal of Accounting, Finance and Business, 2025)
Harumanis mango is known worldwide for its unique flavor and sweet taste thus making Perlis State the major focus for mango production in Malaysia. The unpredictable nature of Harumanis mango production causes severe difficulties for farmers due to its market demand. The inconsistent growth patterns linked to production variability negatively affect farmer incomes and the ability to supply this market. The implementation of sustainable and smart agricultural practices serves as a solution to deliver proper nutrients that will guarantee soil health along with ideal productivity of Harumanis mango trees. The research aims to determine the environmental sustainability levels of Harumanis mango growth in Perlis while also examining farmers willingness to implement sustainable smart agricultural methods. A content analysis of detailed interviews between Harumanis mango farmers and expert researchers determined how farmers approach sustainable farming implementations. This research applies to the Theory of Planned Behavior (TPB) framework to discover behaviour acceptance elements influencing farmers' adaptation decisions. Data analysis shows that Harumanis mango cultivation remains erratic because farmers lack understanding about the actual causes while also lacking enough knowledge to adopt sustainable farming methods. The study shows that cooperative approaches between stakeholders must be implemented to sustain Harumanis mango farming into the future.